The genus Borreria (Spermacoceae, Rubiaceae) in the state of Ceará, Brazil - Almeida Nepomuceno, Francisco Álvaro (2018)
Fil: Almeida Nepomuceno, Francisco Álvaro. Universidade Federal de Pernambuco; Brasil.